Essential Oil of Two Iranian Horehound Species: Marrubium propinquum and Marrubium parviflorum - Sanaz Hamedeyazdan, Masoomeh Zarei, Ayda Salem, Solmaz Asnaashari, Fatemeh Fathiazad (Tabriz University of Medical Sciences, 2017)
Background: Two species of genus Marrubium belonging to the family Lamiaceae, were studied for their volatile components. Methods: The essential oils were extracted from aerial parts of the plants through hydrodistillation using a Clevenger apparatus. Later, CG and CG-MS analysis were applied to assess the chemical components of the essential oils. Results: Analysis of the M. propinquum essential oil resulted in the identification of 22 components, representing 79.6% of the total essential oil that principally contained oleic acid (19%), β-caryophyllene (7.4%) and m-tolualdehyde (5.2%). In the case of M. parviflorum, 20 components were identified, representing 83% of the M. parviflorum essential oil, among them oleic acid (11.8%), α-pinene (10.2%) and germacrene D (9.8%) were the main compounds. Conclusion: Regarding the results of this study in both essential oils after the non terpenoids, sesquiterpene hydrocarbons possessed the uppermost portion of the oils. We found some similarities and differences between M. propinquum and M. parviflorum essential oils and also in comparison with other species of genus Marrubium which might be due to different parameters such as agrotechnical factors.